A multi-Agent framework for funded research supervision - Mahmoud M.A.; Ahmad M.S.; Raveentharan J.K.; Kulasegaran Y.; Jassim O.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer aided instruction; Intelligent agents; Robotics; Software agents; Students; Supervisory personnel; Agent-based systems; Intelligent software agent; Multiagent framework; Related functions; Research supervisions; Student's performance; System administrators; Task management; Multi agent systems